Działania upodmiotawiające w profilaktyce manipulacji wobec seniorów - Lisiecka-Bednarczyk, Agnieszka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article discusses the problematic practice of senior manipulation with the most common fraud technique known as the ‘legend.’ As consumers, senior citizens suffer from fraud attempts undertaken by individuals and groups who make extensive use of psycho-manipulation mechanisms. This article also discusses the needs experienced by senior citizens that are often exploited by fraudsters, and the social influence mechanisms that facilitate manipulation. The analysis is concluded with a review of possibilities for preventive interventions and for empowering attitudes that protect seniors against manipulation.